A reverse-phase protein microarray-based screen identifies host signaling dynamics upon Burkholderia spp. infection - Chiang, Chih-Yuan; Uzoma, Ijeoma; Lane, Douglas J.; Memišević, Vesna; Alem, Farhang; Yao, Kuan; Kota, Krishna P.; Bavari, Sina; Wallqvist, Anders; Hakami, Ramin M.; Panchal, Rekha G. (Frontiers in Microbiology, 2015)
Burkholderia is a diverse genus of Gram-negative bacteria that cause high mortality rate in humans and cattle. The lack of effective therapeutic treatments poses serious public health threats. Insights toward host-Burkholderia spp. interaction are critical in understanding the pathogenesis of the infection as well as identifying therapeutic targets for drug development. Reverse-phase protein microarray (RPMA) technology was previously proven to characterize novel biomarkers and molecular signatures associated with infectious diseases and cancers. In the present study, this technology was utilized to interrogate changes in host protein expression and post-translational phosphorylation events in macrophages infected with a collection of geographically diverse strains of Burkholderia spp. The expression or phosphorylation state of 25 proteins was altered during Burkholderia spp. infections and of which eight proteins were selected for further validation by immunoblotting. Kinetic expression patterns of phosphorylated AMPK-α1, Src, and GSK3β suggested the importance of their roles in regulating Burkholderia spp. mediated innate immune responses. Modulating inflammatory responses by perturbing AMPK-α1, Src, and GSK3β activities may provide novel therapeutic targets for future treatments.